2006
DOI: 10.1682/jrrd.2005.01.0031
|View full text |Cite
|
Sign up to set email alerts
|

Overarching principles and salient findings for inclusion in guidelines for power mobility use within residential care facilities

Abstract: Abstract-Although power mobility has many potential benefits for users, power mobility incidents and accidents are a serious concern. To date, little research has explored power mobility safety, and no gold standard exists to determine whether the user is a safe driver. As a possible alternative to a facility unilaterally imposing regulations on power mobility users, we conducted a research project in which power mobility users and other stakeholders used the Delphi method to develop guidelines for power mobil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 13 publications
2
26
0
Order By: Relevance
“…To determine suitability, prescribers frequently relied on informal and formal assessments of various client attributes, including cognition, vision, hearing, and perception-tests that may have reinforced their expert knowledge but, as some prescribers noted, may also have lacked predictive validity (Mortenson et al, 2005(Mortenson et al, , 2006. Given cognitive and workload demands, prescribers may have used age-based heuristics-that is, problem-solving shortcuts-to help them to make provision decisions quickly and efficiently.…”
Section: Deciding Who Should Be Entitledmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine suitability, prescribers frequently relied on informal and formal assessments of various client attributes, including cognition, vision, hearing, and perception-tests that may have reinforced their expert knowledge but, as some prescribers noted, may also have lacked predictive validity (Mortenson et al, 2005(Mortenson et al, , 2006. Given cognitive and workload demands, prescribers may have used age-based heuristics-that is, problem-solving shortcuts-to help them to make provision decisions quickly and efficiently.…”
Section: Deciding Who Should Be Entitledmentioning
confidence: 99%
“…One descriptive study of scooter prescribers in the Netherlands provided insight into how health care professionals struggled to balance their responsibility to recommend devices on the basis of predetermined criteria with their desire to act in what they perceived as their clients' best interests (Jörg, Boeije, & Schrijvers, 2005). Using a multi-method approach that included a variety of stakeholders (Mortenson et al, 2005(Mortenson et al, , 2006, residential care prescribers developed powered mobility safety guidelines, which indicated that prescribers were aware of the benefits of powered mobility use by residents but also wanted to mitigate the potential harm to users and to others in their facilities.…”
mentioning
confidence: 99%
“…Personalized driving training (Hall, Partnoy, Tenenbaum, & Dawson, 2005), driving performance assessments (Dawson, Chan, & Kaiserman, 1994), and risk management strategies and institutional driving guidelines (Mendoza et al, 2003;Mortenson et al, 2006) are currently applied to minimize unsafe power wheelchair operation and maintain mobility independence in institutional settings. However, these interventions do not always address residents' need for self-mobility, especially in circumstances when driving abilities are marginal or deteriorate and use of power wheelchairs is restricted.…”
Section: Literature Review Current Interventionsmentioning
confidence: 99%
“…39 Power mobility use may also act as a subtle proxy for higher level executive function that our measure of cognition was too crude to discern. Although there are safety concerns associated with the use of power mobility, 5,40 anti-collision power wheelchairs are currently under development for use in these settings. 41 Unlike previous research, 11 SIT scores were not significant independent predictors of mobility.…”
Section: Discussionmentioning
confidence: 99%